(untitled) (REMUNOM, 2025)
The pharmacist plays a fundamental role in the research, production, and promotion of the use of herbal medicines, ensuring their quality, safety, and efficacy. Phytotherapy involves the use of medicinal plants in various pharmaceutical forms and is widely recognized as a therapeutic alternative. This study analyzed the pharmacist’s role within the production chain and in guiding the rational use of herbal medicines. Scientific databases were consulted from 2001 to 2024, including clinical studies, systematic reviews, and regulatory guidelines. The results demonstrate that the pharmacist contributes from the selection of raw materials to the distribution and patient counseling, ensuring product standardization, safety, and proper use. The findings highlight the importance of pharmaceutical involvement in strengthening the rational use of herbal medicines, promoting effective regulations, and expanding the integration of these products into the healthcare system.